Peningkatan Keterampilan Berpikir Kritis dan Karakter Kerjasama Siswa pada Konsep Tumbuhan Melalui LKS Inkuiri Dan Penugasan berbasis Internet di SMA - Norhasanah Norhasanah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2019)
Welcome to the 21st century, teachers are required to have communication skills, cooperation, critical thinking, and creative, this is important in the process of learning in the classroom. One of the appropriate learning media for students to gain knowledge as widely as possible is through the utilization of internet network. The skills of critical thinking and cooperative skills must be continuously trained to the students. Saai is an internet-based assignment in working on LKS still need to be optimized. Therefore, classroom action research is done to improve critical thinking skills and skills of cooperating students on the concept of plants through LKS inquiry and internet based assignment in SMA. The subjects of the students of class X MIA 3 SMAN 4 Barabai were 25 students. Research conducted two cycles, each cycle is done twice a meeting. Data of critical thinking skills (formulating problems, analyzing data, and making conclusions) were scored using rubric of critical thinking skill and skill of cooperation scored using rubric of skill of cooperation, ie score obtained divided by maximum score and expressed by%. The results showed students' critical thinking skills improved. Cycle I obtained a score of 61.67% with good enough category, while in cycle II obtained a score of 80.83% with good category. Skills define the problem very well, while analyzing data and make conclusions pretty well. Skills in student cooperation also increased, the cycle I obtained a score of 53% with good enough category, while in cycle II obtained a score of 87.50% with very good category